Origin and diagenesis of the manetoe facies, southern Yukon and Northwest Territories, Canada. - Aulstead, Kathy Loree (University of Calgary, 1987)
Bibliography: p. 132-142. The Manetoe Facies is a diagenetic feature developed in Lower and Middle Devonian carbonates of the Mackenzie Shelf. The Manetoe Facies is of economic importance in that it forms the reservoir rock for three gas fields and contains lead-zinc mineralization similar in nature to Mississippi Valley-type deposits. The paragenetic sequence of cements is: white sparry dolomite, bitumen, fluorite, anhydrite, barite, calcite, quartz, sphalerite and galena. Dolomite of the Manetoe Facies formed prior to the end of the Devonian in a hydrothermal system. Lateral relations in outcrop indicate that the formation of dolomite cement was contemporaneous with dolomitization of surrounding strata. Fluid inclusion data indicate dolomite cements formed from hot (150-210 °C), hypersaline (18-29 eq. wt. % NaCl) brines. This agrees well with s 10 0 of the dolomite cements (-9 to -16 °/oo PDB), yielding an initial water composition of +3 to +10 °/oo SMOW. Results of experimental stretching of fluid inclusions in dolomite imply that it is unlikely that inclusions in dolomite stretched under conditions of maximum burial. Evidence for dolomitization during the Devonian is provided by extreme changes in conodont colour alteration indices from Devonian to Mississippian samples, the stratigraphic position of the Manetoe Facies (confined to Middle Devonian strata) and the similarity of S 34 S of sulphate in barite and anhydrite cements (which post-date dolomitization) to late Middle to Upper Devonian seawater sulphate. Fluorite cements formed from fluids similar to those causing dolomitization at temperatures near 130°C, as indicated by analyses of fluid inclusions. Barite cements formed from moderately saline fluids {13 eq. wt. % NaCl). Calcite cements formed from hot {110-190°C) fluids whose salinity decreased during precipitation (18-1.7 eq. wt. % NaCl), as determined from fluid inclusion analyses. Oxygen isotope ratios for calcite cements trend toward negative values (to -36 °/oo PDB), which, in association ...